American Growth and Napoleonic Wars - Vergil, Hasan; Ozgur, M. Erdem (Panoeconomicus, 2013)
Four years after the French Revolution, in 1793 a series of wars among France and other major powers of Europe began and they lasted until 1815. There is disagreement among economic historians about the effects of these wars on the trend of US economic growth. This paper aims to answer the following question. Did America as a neutral nation take advantage of economic possibilities caused by Europe at war through trade? To put it differently, this paper questions whether there was an export-led growth due to the war. To answer this question, we re-examined the export-led growth hypothesis for the period 1790-1860 using the ARDL methodology. Based on this methodology, a cointegrated relationship is found among the variables of real GDP, labor, exports and exchange rates. The results suggest that the economic growth of the US was not export-driven. In addition, parallel to the results of unit root tests with structural breaks, the coefficient of the dummy variable was statistically significant in the long run, implying that the war did have a significant effect on the economic growth trend of the US.Key words: Napoleonic wars, United States trade growth, ARDL methodology.JEL: N11, N41, N71.